SASBDB: Towards an automatically curated and validated repository for biological scattering data. (11th October 2019) - Kikhney, Alexey G.; Borges, Clemente R.; Molodenskiy, Dmitry S.; Jeffries, Cy M.; Svergun, Dmitri I.
Abstract: Small‐angle scattering (SAS) of X‐rays and neutrons is a fundamental tool to study the nanostructural properties, and in particular, biological macromolecules in solution. In structural biology, SAS recently transformed from a specialization into a general technique leading to a dramatic increase in the number of publications reporting structural models. The growing amount of data recorded and published has led to an urgent need for a global SAS repository that includes both primary data and models. In response to this, a small‐angle scattering biological data bank (SASBDB) was designed in 2014 and is available for public access at www.sasbdb.org . SASBDB is a comprehensive, free and searchable repository of SAS experimental data and models deposited together with the relevant experimental conditions, sample details and instrument characteristics. SASBDB is rapidly growing, and presently has over 1, 000 entries containing more than 1, 600 models. We describe here the overall organization and procedures of SASBDB paying most attention to user‐relevant information during submission. Perspectives of further developments, in particular, with OneDep system of the Protein Data Bank, and also widening of SASBDB including new types of data/models are discussed.